Exploring Stem Cell Therapy for Burn Wounds: A Review of Current Variations and Advances - Soya Loviana Hasibuan; Syamsul Rizal; Mirnasari Amirsyah; Dewi Fibrini (Green Publisher Indonesia, 2026)
Burn wounds causes disabilities that lower quality of life and productivity, and can even result in death. Therefore, a promising therapy that may accelerate the healing process of burn wounds and prevent disabilities is currently being developed. The sources from international journals obtained through computer-based literature searches by PubMed, ScienceDirect, Springer Link, and Google Scholar. The focus is on publications from the past five years (2019-2024) using keywords such as